Novel difluoroboron complexes of curcumin analogues as "dual-dual" sensing materials for volatile acid and amine vapors. (August 2020) - Li, Ziyong; Song, Yufei; Lu, Zhiqiang; Li, Zixu; Li, Rong; Li, Yunshuang; Hou, Siteng; Zhu, Yan-Ping; Guo, Hui
Abstract: The development of near-infrared difluoroboron complexes of curcumin analogues to specifically detect one or both analytes in the solid state is highly desirable. Herein, three novel BF2 -curcumin analogues with an extended π-conjugation (TBN, TBT and NBN ) have been rationally designed and developed, in which the dimethylamino group acted as electron donator (D) and the proton-binding site, and the BF2 bdk moiety not only functioned as electron acceptor (A) but also responded to amine vapors. And they exhibited excellent solvent-dependent photophysical properties in solutions and PMMA film state. Moreover, BF2 -curcumin analogues TBN and NBN showed an unprecedented "dual-dual" sensing performance (the first dual: simultaneous response to both acid and amine vapors; the second dual: fluorescent turn-on sensing and colorimetric sensing) in solutions and PMMA film state. Therefore, they would be utilized as multifunctional sensing materials for specific detection towards volatile acid and amine vapors in environmental and biological systems. Graphical abstract: Image 1 Highlights: The novel BF2 -curcumin analogues with an extended π-conjugation were developed. They exhibited solvent-dependent photophysical properties in solutions. They showed "dual-dual" sensing behavior towards volatile TFA and amine vapors.